A promising nonlinear optical material and its applications for all-optical switching and information converters based on the spatial self-phase modulation (SSPM) effect of TaSe2 nanosheets. Issue 13 (8th March 2019) - Shan, Youxian; Wu, Leiming; Liao, Yunlong; Tang, Jie; Dai, Xiaoyu; Xiang, Yuanjiang
Abstract : Few-layer TaSe2 nanosheets are prepared by liquid-phase exfoliation, the nonlinear optical response of which is researched based on the spatial self-phase modulation effect. Abstract : Few-layer TaSe2 nanosheets are prepared by liquid-phase exfoliation, the nonlinear optical response of which is researched based on the spatial self-phase modulation effect. The large nonlinear refractive index and the third-order nonlinear susceptibility have been confirmed experimentally. Based on the cross-phase modulation technique, the attractive nonlinear optical responses of 2D TaSe2 nanosheets have been utilized to realize all-optical switching. It is shown that a strong controlling light beam can change the phase of weak signal light, leading to the novel all-optical switching phenomenon. Based on the all-optical switching, we propose information transfer by using a baffle to control the mode of input signal to achieve the synchronized control of the output signal. Our experimental results have great potential applications in all-optical information transmission, all-optical switching, photoelectric detectors, and laser devices.